AI Freelancing Application - Kirubavathy; S., Nithish Narayanan; K., Sandeep S; S., Vetrivelan (Journal of Ubiquitous Computing and Communication Technologies, 2025)
Unemployment is a pressing issue across underrepresented and marginal marketplaces with limited access to employment opportunities. The AI Freelancing Application aims to bridge this gap by predicting artificial intelligence solutions such as Natural Language Processing (NLP) for multilingual chatbot-facilitated conversation exchange, job–talent mapping at the individual level based on AI-based recommendation models, and geolocation-aware algorithms for personalized recruitment. The platform enables freelancers and clients to register, list work, showcase profiles, and interact via an advanced AI-based chatbot. The platform features multiple online and offline payment security options, as well as real-time synchronization to ensure it is always reachable and operational, even with poor network connectivity. The app was utilized by over one user in terms of usability, accessibility, and functionality. Results indicated a high-quality job-matching rate (87%), with the AI-based recommender system effectively matching workers with nearby jobs. The multilingual chatbot performed considerably better in onboarding rates and task completion ratios (82%) for non-English speakers. Pilot user feedback highlighted the ease of use of the platform, the open payment options, and offline support as major positives, and suggested greater integration with certification verification websites. With the competitive advantage of modular design integration, real-time artificial intelligence automation, and human-centered design, the work presented here indicates that the AI Freelancing Application can serve as a driver for economic empowerment, making work accessible and systematically addressing barriers.
Keywords: Freelancing; Artificial Intelligence; Unemployment; Geolocation; Chatbot; Inclusive Employment; Informal Sector; Multilingual NLP